Understanding contraceptive use in Pakistan: The role of individual and community contextual factors - Asifa Kamal; Lamia Alyami; Sadaf Malik; Maryam Siddiqa; Muhammad Ijaz; Afza Rasul; Jamal Abdul Nasir (PLoS ONE, 2026)
Key findings from the PDHS 2017−18 indicate that the total demand for family planning among married women in Pakistan was 52%. Research is needed to understand the persistently low contraceptive use in the country. This study aimed to identify the individual and community-level contextual factors that influence contraceptive use in Pakistan. Data were taken from all four waves of the Pakistan Demographic and Health Surveys (PDHS); 1990−91, 2006−07, 2012−13, and 2017−18. A multi-level logistic regression model was used to estimate the strength of the association between contraceptive use for both individual and community-level factors. The final adjusted model revealed that the likelihood of contraceptive use among women increased from 1991 to 2013 but slightly declined in 2017−18. Specifically, in 2006−07 PDHS, the adjusted odds ratio (AOR = 3.14) of contraceptive use was lower than that in 2012−13 PDHS (AOR = 4.33). In the 2017−18 PDHS, the AOR = 4.02 was slightly lower than that in 2012−13. Contraceptive use was found to be lower among uneducated, older women and those with a low wealth index. This study found that decisions about contraceptive use are shaped by not only individual-level factors but also by community-level factors. Increases in contraceptive use were associated with individual-level characteristics such as women’s age at first cohabitation, education, work status, parity, husband’s education, and wealth index. A major community-level factor contributing to increased contraceptive uptake was community-level education.